(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2006)
Symmetrical zonality in zeolitical dikes of bazaitoid composition is the result of discrete distribution of zeolites in the area. Discreteness can be noted in the form of leaps of changed zeolite deposition along longitudinal protectonic cracks or hidden flow textures. The main reason for symmetrical zonality to occur in the dikes of Alaverdi and Kapan are fields in the fragmental diffusional metamorphism when zeolitization is developed in capillary-porous environment under the conditions of oriented dislocation of chemical elements along many frontal lines, in this particular case, from central axial parts of dikes to contact surface perpendicular to the planes of longitudinal pretectonic cracks. Textures fixed by zeolitization are inherited from primary magmatic hidden flow textures of externally massive homogenous dikes. Black and white vertical exfoliation in rythmic striped dikes, based on the alternation of zeolitized (metasomatic newly formations) and relictic (unchanged primary rocks) zones in essence heterogenous is the result of magmatic and metasomatic processes.